Comparison of nutrient content and cost of home-packed lunches to reimbursable school lunch nutrient standards and prices - Johnson, Cara M.; Bednar, Carolyn; Kwon, Junehee; Gustof, Alissa (My University, 2010)
The purpose of this study was to compare nutrient content and cost of home-packed lunches to nutrient standards and prices for reimbursable school lunches. Researchers observed food and beverage contents of 333 home packed lunches at four north Texas elementary schools. Nutritionist Pro was used to analyze lunches for calories, total fat, saturated fat, protein, fiber, vitamin A, vitamin C, calcium, iron, fiber, and sodium content. These values were then compared to National School Lunch Program (NSLP) standards and other nutrient standards. Cost of each home-packed lunch was estimated based on food prices at three local supermarkets. A one-sample t-test (p = 0.05) was used to compare nutrient values of home packed lunches to National School Lunch Program (NSLP) standards. A paired t-test was used to compare cost of home packed lunches to each school’s full price for a reimbursable school lunch. Home packed lunches differed significantly from NSLP nutrient standards, containing fewer calories, more sodium, and less vitamin A, calcium, iron, and dietary fiber. Mean cost of home- packed lunches at 3 of the 4 schools was significantly less than the sales price for the reimbursable school lunches. Reimbursable school lunches provided by schools participating in the NSLP provide overall healthier meals for children than most home-packed lunches. Parents should be made aware of the nutritional benefits of school meals.
Keywords: Elementary schools; National School Lunch Program; Home-packed lunches; Reimbursable school lunches; Nutrition; Cost